“United we stand, divided we fall”: Sovereignty and Government during the Greek Revolution, 1821–1828 - Sotiropoulos, Michalis (Historein, 2022)
This article explores the political languages which Greek revolutionaries employed between roughly 1821 and 1828, and the multiple ways in which these languages found their way into the political projects they put into force (or sought to do so). It does so by considering the revolution as an open-ended political crisis during which revolutionaries were forced to address – theoretically and practically – the fundamental issues of political power: its source, its location and its organisation. As it shows, the frameworks for political action (or “scripts”) the revolutionaries drew on varied and fed into alternative visions of statehood (national, federal, local). By uncovering and understanding these alternatives, as well as why some predominated over others, the article aims to: propose an alternative genealogy of “the political” in the Greek revolution; shed new light on the liberalism(s) of the Revolution; and bring the perspective of the Greek world into the discussion about the importance of the revolutionary wave of the 1820s.